Influence of Urinary Incontinence Related Factors on Health-Related Quality of Life in Patients with Chronic Obstructive Pulmonary Disease: A Cross-Sectional Study - Alrajhi NS; Albarrati A; Aldhahi MI; Gwada RF (International Journal of COPD)
Nada Saleh Alrajhi,1 Ali Albarrati,2 Monira I Aldhahi,3 Rehab FM Gwada2,4 1Physical Therapy Department, Prince Sultan Military Medical City, Riyadh, Saudi Arabia; 2Rehabilitation Health Sciences Department, College of Applied Medical Sciences, King Saud University, Riyadh, Saudi Arabia; 3Department of Rehabilitation Sciences, College of Health and Rehabilitation Sciences, Princess Nourah bint Abdulrahman University, Riyadh, Saudi Arabia; 4Physical Therapy Department, National Heart Institute, Giza, EgyptCorrespondence: Monira I Aldhahi, Department of Rehabilitation Sciences, College of Health and Rehabilitation Sciences, Princess Nourah bint Abdulrahman University, P.O. Box 84428, Riyadh, 11671, Saudi Arabia, Email mialdhahi@pnu.edu.saPurpose: Chronic obstructive pulmonary disease (COPD) is a progressive respiratory condition marked by airflow limitation and symptoms like chronic cough, breathlessness, and chest tightness. These factors, along with exacerbations and polypharmacy, may predispose COPD patients to urinary incontinence (UI). Unique challenges such as increased intra-abdominal pressure, pelvic floor weakness, and comorbidities may worsen UI and impair health-related quality of life (HRQoL). This study aimed to identify factors associated with UI severity in COPD patients and to examine its impact on HRQoL.Methods: This cross-sectional study included 101 participants diagnosed with COPD who were reported to have UI. Participants completed the following questionnaires: the health status and UI severity were recorded using the COPD Assessment Test (CAT), International Consultation on Incontinence Questionnaire- Urinary Incontinence – short form (ICIQ-UI short form), and Incontinence Impact Questionnaire – short form (IIQ-7).Results: UI severity was correlated with age, BMI, smoking, comorbidities, medications, chest tightness, and breathlessness. Severe UI predictors included age (OR=1.07), BMI (OR=1.09), and number of medications (OR=5.04), whereas breathlessness predicted moderate (OR=1.72) and severe UI (OR=1.87). Among COPD patients, 82.2% reported a mild impact of UI on HRQoL, and 6.9% reported a severe impact. Notably, among those experiencing moderate-to-severe HRQoL impairment, 63.6% had severe UI.Conclusion: This study highlights urinary incontinence (UI) as a prevalent and impactful comorbidity in individuals with COPD, significantly affecting their HRQoL. UI severity was associated with clinical factors such as older age, higher body mass index (BMI), greater medication burden, and breathlessness. Notably, greater UI severity corresponded to more substantial impairments in HRQoL, with severe cases reporting greater negative effects on daily functioning. These findings underscore the importance of routine screening for UI in COPD patients and the implementation of targeted continence care strategies to enhance overall quality of life.Plain Language Summary: This study highlights significant correlations between UI, HRQoL, and factors such as age, BMI, and breathlessness. This study emphasizes the need for routine UI screening in patients with COPD to improve HRQoL through specialized continence care.Keywords: COPD, disease severity, health-related quality of life, urinary incontinence